2017
DOI: 10.18782/2320-7051.2499
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Planting Density and Different Genotypes on Growth, Yield and Quality of Guar

Abstract: INTRODUCTION Cluster bean (Cyamopsis tetragonoloba (L.) Taub.), commonly known as guar, belonging to the family Leguminosae is an indigenous, annual and self-pollinated legume crop grown for feed, green fodder, vegetable, green manuring and gum extraction from seed. Being drought hardy, it is grown mainly under rainfed conditions in India since ancient times. It is primarily grown for its tender green pods in arid and semi arid regions of our country and is a good source of carbohydrates, protein, fiber and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…Therefore, the optimal and desirable density, i.e., the distances between rows of 45 cm, is the best density for this plant and it is recommended that the results of Patel et al (2002), who showed the highest yield in the row spacing of 45 cm be consistent. The results of researchers' studies on three planting densities (22, 15 and 33 plants per square meter) of guar gum showed that the density of 33 plants per square meter increased the percentage of gum (galactomannan) protein, the height of bush, the number of leaves, the number of pods, the number of seeds per pod, 100 seed weight, pod length, seed yield compared to other densities (Nandini et al, 2017). The results showed that the application of the full recommended dose of fertilizers (15 kg N ha -1 + 40 kg P 2 O 5 ha -1 ) significantly increased the seed and straw yields of cluster beans (guar gum) by 55.7 and 60.9 per cent over control, respectively Kumawat et al (2006).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the optimal and desirable density, i.e., the distances between rows of 45 cm, is the best density for this plant and it is recommended that the results of Patel et al (2002), who showed the highest yield in the row spacing of 45 cm be consistent. The results of researchers' studies on three planting densities (22, 15 and 33 plants per square meter) of guar gum showed that the density of 33 plants per square meter increased the percentage of gum (galactomannan) protein, the height of bush, the number of leaves, the number of pods, the number of seeds per pod, 100 seed weight, pod length, seed yield compared to other densities (Nandini et al, 2017). The results showed that the application of the full recommended dose of fertilizers (15 kg N ha -1 + 40 kg P 2 O 5 ha -1 ) significantly increased the seed and straw yields of cluster beans (guar gum) by 55.7 and 60.9 per cent over control, respectively Kumawat et al (2006).…”
Section: Resultsmentioning
confidence: 99%
“…Yield components are also affected by plant density. The results of researchers' investigations on three planting densities (22, 15 and 33 plants per square meter) of guar showed that the density of 33 plants per square meter increased the percentage of gum (galactomannan), protein, plant height, number of leaves, number of pods, number of seeds per pod, The weight of 100 seeds, pod length, seed yield were compared with other concentrations (Nandini et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…En la respuesta del guar al distanciamiento entre surcos, se ha observado que en surcos estrechos ocurre una mayor intercepci贸n de radiaci贸n solar como resultado de una mejor distribuci贸n de las plantas en el terreno, situaci贸n que provoca un crecimiento del cultivo m谩s vigoroso y mayor n煤mero de ramas, hojas y 贸rganos reproductivos que los observados en surcos con mayor distanciamiento (Nandini et al, 2017). Bajo estas condiciones ocurre una tendencia a incrementarse el rendimiento de semilla en surcos estrechos (30 cm) respecto a surcos a 45 y 60 cm (Akhtar et al, 2012;Ramanjaneyulu et al, 2018).…”
Section: Introductionunclassified
“…According to the findings of Kalyani & Sunitha (2011), when compared to other sowing dates (the first and second fortnights of the months of July and August), the first fortnight of July performed noticeably better than the other sowing dates. In addition, Nandini et al (2017) reported that the planting date of the 10 th of July had resulted in a greater number of pods per plant and grain per pod than any early or late planting date. The evaluation of 22 different guar genotypes also revealed that the gum content varied slightly (from 28.47 percent to 32.89 percent) depending on the ecotype but was not affected by the climate.…”
Section: Introductionmentioning
confidence: 99%